Traceless Solid-Phase Synthesis of 1' H-Spiro[Pyrrolidine-3,2'-quinazolin]-2-ones and 1' H-Spiro[Piperidine-3,2'-quinazolin]-2-ones via Lactamization of 1,2-Dihydroquinazoline-2-carboxylates - Pospíšilová, Jana; Krchňák, Viktor; Schütznerová, Eva (ACS combinatorial science, 2019)
We present the solid-phase synthesis of 1,2-dihydroquinazoline-2-carboxylate derivatives with a quaternary carbon in position 2 and their subsequent cyclization in solution into compounds with unique 3D architectures and pharmacological relevance-spiroquinazolines, namely, 1' H-spiro[pyrrolidine-3,2'-quinazolin]-2-ones and 1' H-spiro[piperidine-3,2'-quinazolin]-2-ones. Acyclic precursors were prepared from commercially available building blocks: protected amino acids (2,4-diaminobutyric acid and ornithine), 2-nitrobenzensulfonyl chlorides and α-bromoacetophenones. The crucial step of the synthesis was a base-mediated tandem reaction including C-arylation followed by cyclization into indazole oxides, and the formation of a 5-membered heterocycle was accomplished by ring expansion into quinazolines. These derivatives were cyclized into spiro compounds in solution after cleavage from the resin.
Keywords: aminobutyráty; pyrrolidiny; Ornithine; Solid-Phase Synthesis Techniques; Quinazolines; Spiro Compounds; Pyrrolidines; Nitrobenzenes; Cyclization; ornithin; Piperidines; chinazoliny; techniky syntézy na pevné fázi; Aminobutyrates; nitrobenzeny; cyklizace; spirosloučeniny; Acetophenones; piperidiny; acetofenony